2007
DOI: 10.1242/jcs.010389
|View full text |Cite
|
Sign up to set email alerts
|

The RASSF1A tumor suppressor

Abstract: RASSF1A lacks apparent enzymatic activity but contains a Ras association (RA) domain and is potentially an effector of the Ras oncoprotein. RASSF1A modulates multiple apoptotic and cell cycle checkpoint pathways. Current evidence supports the hypothesis that it serves as a scaffold for the assembly of multiple tumor suppressor complexes and may relay pro-apoptotic signaling by KRas. RASSF1A is part of a family of potential tumor suppressorsRASSF1A is a member of a family of six related proteins, each of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
457
2
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(488 citation statements)
references
References 115 publications
14
457
2
15
Order By: Relevance
“…Significantly, mammalian homologs of each component of the Drosophila Hippo-LATS pathway have been identified [Fat4 for Fat, Merlin for Merlin, Ex for Ex, RASSF1A for dRASSF, hWW45 for Sav, Mst1 and Mst2 for Hippo, LATS1 and LATS2 for LATS, MOB1 (Msp1 one binder) for Mats, and YAP (Yesassociated protein) and TAZ (transcriptional coactivator with PDZ-binding motif) for Yorkie] (12). We and others recently showed that part of the Hippo-LATS signaling pathway discovered in Drosophila are conserved in mammals and that many members of the pathway could be confirmed as either tumor suppressors (Fat4, Merlin, RASSF1A, Mst1/2, LATS1/2, MOB1) or oncogenes (YAP and TAZ) in human cancers (15)(16)(17)(18)(19). Therefore, further characterization of Hippo-LATS pathway and its regulators in mammals will have great implication for not only our understanding the molecular mechanism of tumorigenesis, but also for future targeting of this pathway for cancer therapies.…”
Section: T7-r1(d505v)-yfp 35s:plc2-cfpmentioning
confidence: 97%
“…Significantly, mammalian homologs of each component of the Drosophila Hippo-LATS pathway have been identified [Fat4 for Fat, Merlin for Merlin, Ex for Ex, RASSF1A for dRASSF, hWW45 for Sav, Mst1 and Mst2 for Hippo, LATS1 and LATS2 for LATS, MOB1 (Msp1 one binder) for Mats, and YAP (Yesassociated protein) and TAZ (transcriptional coactivator with PDZ-binding motif) for Yorkie] (12). We and others recently showed that part of the Hippo-LATS signaling pathway discovered in Drosophila are conserved in mammals and that many members of the pathway could be confirmed as either tumor suppressors (Fat4, Merlin, RASSF1A, Mst1/2, LATS1/2, MOB1) or oncogenes (YAP and TAZ) in human cancers (15)(16)(17)(18)(19). Therefore, further characterization of Hippo-LATS pathway and its regulators in mammals will have great implication for not only our understanding the molecular mechanism of tumorigenesis, but also for future targeting of this pathway for cancer therapies.…”
Section: T7-r1(d505v)-yfp 35s:plc2-cfpmentioning
confidence: 97%
“…RASSF1A, 1C, 5 and 7 have been demonstrated to associate with the microtubular network (Moshnikova et al, 2006(Moshnikova et al, , 2008Donninger et al, 2007;Sherwood et al, 2008;Richter et al, 2009). All have been shown to associate with centrosomal elements and, in the case of RASSF1A, with a-, g and b-tubulins.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically, RASSF1A is also the best-characterized member of the group. RASSF1A is a bona fide tumor suppressor gene; RASSF1A knockout mice are prone to tumor development (Tommasi et al, 2005;van der Weyden et al, 2005), whereas RASSF1A protein is involved in microtubule stability, cell cycle progression, regulation of apoptosis, cell migration and forms a part of the mammalian Hippo tumor suppressor network (Donninger et al, 2007;Hesson et al, 2007b;Dallol et al, 2009). Some of the classical RASSF members have been shown to bind RAS proteins and hence may act as RAS effectors.…”
Section: Introductionmentioning
confidence: 99%